ChemInform Abstract: 4‐R‐7‐Nitrobenzofurazans in [3 + 2] Cycloaddition Reactions with N‐Methylazomethine Ylide. Issue 15 (25th March 2013) - Pechenkin, S. Yu.; Starosotnikov, A. M.; Bastrakov, M. A.; Glukhov, I. V.; Shevelev, S. A.
Abstract A number of novel tetrahydroisoindole derivatives (IV) fused with a furazan ring are stereoselectively synthesized based on the 1, 3‐dipolar cycloaddition of in situ generated N‐methylazomethine ylide with substituted 4‐nitrobenzofurazans.